Metabolic Response in the Gill of Portunus trituberculatus Under Short-Term Low Salinity Stress Based on GC-MS Technique - Wang, Jiali; Liu, Qi; Zhang, Xinni; Gao, Gao; Niu, Mingming; Wang, Huan; Chen, Lizhi; Wang, Chunlin; Mu, Changkao; Wang, Fangfang (Frontiers in Marine Science, 2022)
Salinity is an important factor affecting the survival, growth, and metabolism of marine crustaceans. Low-salt stress will result in the death of swimming crabs. This paper investigates the metabolic response in the gills of Portunus trituberculatus under short-term low-salt stress by comparing the metabolic molecules in the four salinity treatment groups (24‰, 16‰, 12‰, and 8‰) by GC-MS technique. In this study, nine common differential metabolites such as pyruvate, malic acid, and phosphoethanolamine were found in the gill tissues of crabs. KEGG enrichment analysis revealed that six metabolic pathways, including the citric acid cycle, pyruvate metabolism, and the HIF-1 signaling system, were significantly impacted by low salt stimulation. According to the findings, salinity 12‰ is a critical node in crab adaptation to low salinity. In the process of adaptation to short-term low-salinity environment, amino acids participated in osmotic regulation, and organic acids such as pyruvate and malic acid were involved in energy metabolism to ensure their energy supply. This research further enriched the theory of osmotic regulation and metabolic mechanism of adaptation to low salt in crustaceans, with the goal of providing guidance for the improvement of culture technique in Portunus trituberculatus.